Against legalising female ‘circumcision’ of minors: a reply to ‘The prosecution of Dawoodi Bohra women’ by Richard Shweder - Earp, BD (Bristol University Press, 2022)

(untitled)
Defenders of male circumcision increasingly argue that female ‘circumcision’ (cutting of the clitoral hood or labia) should be legally allowed in Western liberal democracies even when non-consensual. In his target article, Richard Shweder (2022) gives perhaps the most persuasive articulation of this argument to have so far appeared in the literature. In my own work, I argue that no person should be subjected to medically unnecessary genital cutting of any kind without their own informed consent, regardless of the sex characteristics with which they were born or the religious or cultural background of their parents. Professor Shweder and I agree that Western law and policy on child genital cutting is currently beset with cultural, religious and sex-based double standards. We disagree about what should be done about this. In this commentary, I argue that ‘legalising’ childhood FGC so as to bring it into line with current treatment of childhood MGC is not an acceptable solution to these problems. Instead, all medically unnecessary genital cutting of non-consenting persons should be opposed on moral and legal grounds and discouraged by all appropriate means.